Telaah Kelayakan Buku Teks Mata Pelajaran Bahasa Jawa SMP di Kota Semarang Tahun Pelajaran 2019-2020 - Sulanjari, Bambang; Alfiah, Alfiah; Sunarya, Sunarya; Zaidah, Nuning (Universitas PGRI Semarang, 2021)
Textbooks are a basic requirement in learning. The availability of adequate textbooks determines the quality of learning. The Javanese textbooks used in learning, although generally stated to have met the standards by the government, need to get a feasibility assessment related to curriculum changes and 21st-century learning challenges. This study aims to describe the suitability of the contents of the Javanese textbooks for SMP in Semarang city with 2013 curriculum changes and 21st-century learning challenges.This research was conducted in the city of Semarang for 3 (three) months, starting from October to December 2019. The data in this study is evidence of the suitability of the contents of Javanese textbooks for junior high schools on the demands of 21st-century learning. The sources of data in this study are Junior high school Javanese language textbooks used in learning Javanese in the city of Semarang. The books are Marsudi Basa lan Sastra Jawa published by publishers Erlangga and Padha Bisa Basa Jawa published by Yudhistira publishers. Data collection techniques using document studies and interviews. Qualitative data analysis is inductive, that is analysis based on the data obtained. The data analysis step is data reduction, data presentation, and drawing conclusions, the three of which run alongside the research process.The results of this study indicate that the three textbooks are feasible to be used as textbooks in school with some notes. At present, the indicators need to be modified again by the teacher so that they meet good indicator standards. In terms of song material, the teacher needs to find other references to interpret the song text.